Biografia dorosłego dziecka – doświadczenie parentyfikacji i jej konsekwencje - Chojnacka, Barbara (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article concerns the phenomenon of parentification, i.e. the reversal of the roles in the family. The author presents this phenomenon, its course, accompanying mechanisms and consequences as based upon a case study – biography. The experience of inversion of parental roles is often latent and invisible, and is associated with the hidden drama of numerous children, but realised only in adulthood. These „little heroes” become „adult children” who carry on their shoulders burden (usually of emotional nature) of responsibility for their parents and family.
Keywords: family; family home experience; reversal of the roles in the family